Obsessive-Compulsive Disorder in Women - Torres, Albina R. [UNESP]; Torresan, Ricardo C. [UNESP]; de Mathis, Maria Alice; Shavitt, Roseli G. (My University, 2020)
Obsessive-compulsive disorder (OCD) is a chronic, debilitating, and heterogeneous condition that affects 2-3% of the general population. Previous studies have suggested that sex plays a role in OCD phenotypic expression. This chapter aims to review the literature regarding OCD in women, exploring sex differences in (1) the prevalence of OCD/subclinical OCD in nonclinical populations; (2) age of onset, clinical course, and severity and impact of OCD symptoms; (3) onset or aggravation of OCD symptoms among women according to the time point in the reproductive cycle; (4) OCD symptom contents; (5) psychiatric comorbidity; and (6) treatment-seeking behavior and treatment response. Studies report either a slight female predominance or a similar prevalence of OCD in adults from the general population. Women are more likely than men to be married, to present later onset, and to report preceding stressful life events. Onset or worsening of OCD symptoms during pregnancy and postpartum are frequently described. Women are more likely to present contamination obsessions and/or cleaning rituals and comorbid eating and impulse-control disorders. Several interacting mechanisms are probably responsible for mediating the effects of sex/gender in the biological and psychosocial risk factors for OCD. Sex is a relevant factor that should be taken into account when evaluating OCD patients, but more studies are necessary to determine whether or not it defines a valid OCD subtype.
Keywords: Clinical characteristics; Gender; Obsessive-compulsive disorder; Phenomenology; Phenotype; Sex; Sex differences